User Experience Evaluation Framework for Malaysian E-government Mobile Applications : A Participatory Design-infused approach - Emmy Hossain, Hossain (The Association for Computing Machinery (ACM), 2024)
This proposal outlines a research on user experience evaluation frameworks, specifically for the Malaysian e-government mobile applications. The primary objective is to propose a comprehensive framework for user experience evaluation, taking into consideration the cultural aspects. In order to achieve this, the research will employ a mix of both qualitative and quantitative methods, with participatory design infused in the research design. The evaluation framework and recommendations from this research can be used by those who are involved in producing e-government mobile applications.